(untitled) (Journal of Dhaka National Medical College & Hospital, 2026)
Background: Background: According to the World Health Organization (WHO), dementia has become a public health concern due to its significant economic burden on families and nations. However, similar to many developing countries, limited information exists regarding the demographics, clinical characteristics, and comorbidities of dementia patients in Bangladesh. Objective: To examine the clinical and demographic profile of dementia patients at a tertiary-level hospital in Sylhet, Bangladesh. Methods: This observational study included patients with mild to moderate dementia who attended the outpatient Neurology clinic at Sylhet MAG Osmani Medical College, Bangladesh, between July 2017 and June 2018. Data were obtained through face-to-face interviews using a semi-structured questionnaire. Results: The study comprised 71 patients, with a mean age of 62±7.02 years; 53.5% were male, 50.7% resided in rural areas, and 95.7% identified as Muslim. The average duration of illness was 25.20±9.25 months. Vascular dementia (VaD) was the most frequently diagnosed subtype, accounting for 47.9% of cases. Various risk factors (e.g., smoking, hypertension, stroke) were identified in 64.79% of patients. The baseline MMSE score prior to treatment was 14.39±2.95, improving to 19.95±3.50 after 12 weeks of treatment (p<0.001). Conclusion: This study offers baseline data on dementia patients, including mean age, gender distribution, sociodemographic background, dementia subtypes, and observed treatment response. J. Dhaka National Med. Coll. Hos. 2025; 31 (02): 07-11